2015
DOI: 10.2196/resprot.4035
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Telehealth Intervention for Adults With Insulin-Requiring Diabetes: Early Results of a Mixed-Methods Randomized Controlled Trial

Abstract: BackgroundThe role of technology in health care delivery has grown rapidly in the last decade. The potential of mobile telehealth (MTH) to support patient self-management is a key area of research. Providing patients with technological tools that allow for the recording and transmission of health parameters to health care professionals (HCPs) may promote behavior changes that result in improved health outcomes. Although for some conditions the evidence of the effectiveness of MTH is clear, to date the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…It is possible that prolonged use with the accelerometers or e-diaries would cause a change in behavior not observed after only one week and this possibility should be tested in future studies. However, research would predict that the greatest reactance would occur while the device was still novel and the influence of the device would actually reduce over time (Baron, Hirani, & Newman, 2015). Overall, the fact that neither the e-diaries nor the accelerometers increased self-reports of vigorous intentional PA or frequency of discrete exercise sessions is a promising result for researchers who want to use these methods to observe exercise, at least in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that prolonged use with the accelerometers or e-diaries would cause a change in behavior not observed after only one week and this possibility should be tested in future studies. However, research would predict that the greatest reactance would occur while the device was still novel and the influence of the device would actually reduce over time (Baron, Hirani, & Newman, 2015). Overall, the fact that neither the e-diaries nor the accelerometers increased self-reports of vigorous intentional PA or frequency of discrete exercise sessions is a promising result for researchers who want to use these methods to observe exercise, at least in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…All outcomes will be assessed again at 6 months. Intervention usability is an additional secondary outcome which will be evaluated at the end of study as measured by an adapted version of the Mobile App Rating Scale [28] (refer to Fig. 3 for adapted version) and application utilization data collected routinely collected through the application.…”
Section: Methodsmentioning
confidence: 99%
“…The 9-month RCT during which data were collected was conducted in a diabetes clinic in the London borough of Newham, United Kingdom (UK). Details of the study protocol are described elsewhere (19).…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria are listed in Box 1, and the target sample size was 248 (19). An electronic database was used to record the number of potentially eligible patients identified, number of patients invited to the study, number of patients approached, number of exclusions and refusals, and reasons reported, and number of patients enrolled to the study.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation